Religious, socio-cultural norms and gender stereotypes influence uptake and utilization of maternal health services among the Digo community in Kwale, Kenya: a qualitative study - Vernon Mochache; George Wanje; Lucy Nyagah; Amyn Lakhani; Hajara El-Busaidy; Marleen Temmerman; Peter Gichangi (BMC, 2020)
Abstract Background Maternal health outcomes in resource-limited settings are typically influenced by supply-side factors affecting the provision of quality health services. The extent to which demand-side factors contribute to this influence is unclear. We aimed to explore how individual and community-wide factors influenced uptake and utilization of maternal health services among the Digo community residing in Kwale County of coastal Kenya. Methods Between March and December 2015, we conducted 5 focus group discussions (FGDs) and 15 in-depth interviews (IDIs) with members of the Digo community predominant in Kwale county, Kenya. Respondents were sampled purposively and included female (pregnant and postpartum) as well as male adult community members. A thematic content analytic approach was used. Results There were a total of 47 FGD respondents, including 15 (32%) females with a median (interquartile, IQR) age of 38 (27-55) years and 6 (3-8) children. Majority (40%) reported attaining secondary-level education. All IDI respondents were female with a median (IQR) age of 27 (24-35) years and 4 (2-5) children. Majority (80%) had attained primary-level education. We found that religious and socio-cultural norms as well as gender stereotypes were important influences on the uptake and utilization of maternal health services, including facility-based delivery and contraception. Key amongst this was the unspoken deference to the counsel of a prominent matriarchal figure in the decision-making process. Conclusions Among the Digo community of coastal Kenya, a unique social-cultural context comprising of a religious and gendered value belief system influences women's reproductive health and rights. These findings highlight the important role of demand-side factors in influencing maternal health outcomes. In addition to addressing supply-side factors, programs in such settings should aim to address factors that leverage inherent social capital to drive demand for maternal health services ensuring that they are not only effective, but also responsive to the local context.